The Effectiveness of Team Games Tournament Assisted By Quizizz Application to Increase Student Learning Independence - Firdiawan Ekaputra (PT Mattawang Mediatama Solution, 2023)
The objective of this study was to determine whether team games tournaments supported by the quizizz application improved student learning independence. Students from the Jambi University Chemistry Education Study Program took courses in chemistry mathematics in classes A and B in the 2023/2024 academic year. This study is a quasi-experimental study with a non-equivalent group design, with class A as the control class and class B as the experimental class. A questionnaire was used to collect data on students' learning independence both before and after the team games event that was made possible by the Quizizz application to make sure the data from both groups were homogeneous and normally distributed, the initial independent data from both sample classes were checked for both normality and homogeneity. The independent-samples t test is then used to compare data on students' learning independence before and after the team games tournament with the use of the Quizizz application. A significant value of 0.005 in the independent-samples t test results indicated that there was an increase in student learning independence following the implementation of the team games tournament supported by the Quizizz application. Based on these findings, the study came to the conclusion that enhancing student learning independence might be achieved through the use of the Quizizz app in conjunction with a team games event.